Preparing for Demo Day at a Startup Accelerator - Claude Rosental (Revue d'anthropologie des connaissances)
Startup accelerator programs generally host cohorts of entrepreneurs for a few months and conclude with a celebratory event called “demo day.” During this event, entrepreneurs deliver a short presentation of their companies in front of an audience that includes potential investors. This article explores how these entrepreneurs prepare for demo day as part of their curriculum at one Israeli startup accelerator. Based on ethnographical observations of the preparation process, it shows how pitches come to life in a collective and iterative way under the guidance of coaches in communications, and how the latter’s practical advice and approach involve techno-rhetoric, use of a template and problem-solution schema, as well as common marketing tools and registers. It thereby sheds light on the nature and amount of resources invested in some of the dynamics of the demonstration society.